Animal forms - Jeffery, John; Billington, Nigel (London : Longman, 1984)
This book contains a collection of animal engravings-fish, birds, butterflies, crustacea and others, the engravings are startinf points form which exciting individual designs can be developed: some of the crafts in which they can be used are